Versatile cold atom target apparatus - Götz, Simone Andrea; Höltkemeier, Bastian; Hofmann, Christoph S.; Litsch, Dominic; Weidemüller, Matthias (Review of scientific instruments, 2012)
We report on a compact and transportable apparatus that consists of a cold atomic target at the center of a high resolution recoil ion momentum spectrometer. Cold rubidium atoms serve as a target which can be operated in three different modes: in continuous mode, consisting of a cold atom beam generated by a two-dimensional magneto-optical trap, in normal mode in which the atoms from the beam are trapped in a three-dimensional magneto-optical trap (3D MOT), and in high density mode in which the 3D MOT is operated in dark spontaneous optical trap configuration. The targets are characterized using photoionization.